Comparison of children with acute flaccid myeltis before and after 2014. Issue 5 (October 2020) - Marcus, Lydia; Singh, Sumit; Ness, Jayne
Abstract : Objective: To observe whether cases of acute flaccid myelitis (AFM) before and since August 1, 2014, had important differences and to further characterize patients with AFM regarding clinical, laboratory, imaging, and treatment findings. Methods: All pediatric patients with AFM at our institution were reviewed. Demographic, clinical, and diagnostic data were collected through medical record review. Patients with onset before August 1, 2014, and after that date were compared and when applicable compared with Centers for Disease Control and Prevention data. Results: Sixteen patients were included, 6 in the pre-2014 and 10 in the post-2014 group. The mean age in the pre-2014 group was 7.4 years and in the post-2014 group was 6.4 years. Initial symptoms were similar in both groups, as were functional and motor abilities at disease nadir and the most recent follow-up. Post-2014 patients had a higher mean CSF white blood cell count (57) and neutrophil count (30%) compared with pre-2014 patients (3.2 and 0.5%, respectively). Eighty percent of post-2014 patients had positive enterovirus/rhinovirus testing, with 57% of specimens positive for enterovirus D68 (EV-D68). On acute imaging, a triad of brainstem, cervical cord gray matter involvement, and ventral nerve root/cauda equina (CE) thickening/enhancement was found in 5 patients. Conclusion: The groups had more similarities than differences but with a more inflammatory picture in the post-2014 patients. The constellation of cervical cord gray matter, brainstem, and nerve root/CE thickening should raise suspicion for AFM in the appropriate clinical setting. Most post-2014 patients had associated enterovirus infections, and over half tested for EV-D68 were positive. There was minimal clinical improvement in both groups despite various immunotherapies.